Tradition meets innovation: Malay symbols (Tanggam) in contemporary sculpture - An analysis of Hilal Mazlan's kinetic sculpture (Labyrinth) - Mohamad Yusoff, Aiman Yusri; Syed Abu Bakar, Syed Alwi; Tahir, Azian; Omar, Aznan (Universiti Teknologi MARA, Perak, 2025)
This research studies Hilal Mazlan's kinetic sculpture “Labyrinth”, specifically how he reinterprets the Tanggam woodworking technique in contemporary art. Tanggam, renowned for its complex craftsmanship and cultural significance, is changed in Hilal's work by movement, resulting in dynamic sculptures that engage both visually and philosophically. This study employs a qualitative research method, combining primary and secondary data to examine the function of Tanggam in Hilal's art. Edwin Panofsky's iconological framework is used to interpret its symbolic meaning, but the work's kinetic nature presents complications. Kinetic sculptures, unlike static visual art, grow in real time, making it a bit impossible to apply Panofsky's organised three-tier analysis pre-iconographic, iconographic, and iconological because meaning can change based on movement, interaction, and spatial perception. While this study emphasises Hilal's approach to combining legacy and modernity, future research should look into alternative analytical frameworks that are better suited for kinetic and interactive artworks.